UEFA Women`s Elite Club Injury Study: a prospective study on 1527 injuries over four consecutive seasons 2018/2019 to 2021/2022 reveals thigh muscle injuries to be most common and ACL injuries most burdensome - Hallén, A.; Tomás, R.; Ekstrand, J.; Bengtsson, H.; Van den Steen, E.; Hägglund, M.; Waldén, M. (British Journal of Sports Medicine, 2024)
Objective Injuries in women`s football (soccer) have scarcely been investigated, and no study has been conducted in the highest competitive level involving club teams from different countries. Our aim was to investigate the time-loss injury epidemiology and characteristics among women`s elite football players over four seasons.